INVESTIGATING THE GEOMETRIC AND DYNAMIC DIMENSIONS OF SEGNER-TYPE JET TURBINES FOR LOW-PRESSURE WATER SOURCES USING MATHEMATICAL MODELING - Mirsoli O. Uzbekov; Sanjarbek R. Urmonov (Web of Journals Publishing, 2024)
Today, the production of electricity from renewable energy sources is a priority for all countries. Specifically, there is extensive scientific research being conducted on the effective use of small and low-pressure water sources for electricity generation. This research focuses on the creation and improvement of hydropower devices in numerous leading scientific and higher educational institutions worldwide. This article investigates a jet turbine based on a Segner wheel operating in low-pressure water sources.The study examines how the geometric shape and the number of nozzles of a hydraulic turbine affect the speed and pressure changes of a moving water flow at various points. This analysis is performed through mathematical modeling using COMSOL Multiphysics version 6.1 (Build: 282), which employs a standard RANS method for nozzles of five different geometric shapes in the CFD module, specifically in the Turbulent Flow, k-ε model.To determine the optimal geometric shape of the nozzle, the study divided the water at the nozzle inlet into water bundles. Triangles were formed based on the impact direction of each water clot on the nozzle's inner walls, directed toward the center of the outlet. These were determined by the horizontal coordinates of the impact points of each water clot on the nozzle. Modeling was conducted in both two- and three-dimensional spaces, utilizing the k-ε model in an automated system specifically designed for plane shear layers and turbulent flows. This model includes the smallest set of equations to minimize unknown quantities in processes involving all natural heat and liquid flows.The study achieved favorable results when calculating shear stresses and Reynolds tensors for a medium with a small pressure gradient. The initial kinematic and dynamic parameters used in the model were determined based on formulas discussed in the previous chapter.
Keywords: Micro hydroelectric power plant, jet turbine, nozzle, guide device, turbine impeller, groundwater level, water density, water column, viscosity, cavitation.